Family Dinners & Youth Risk Behaviors among African-Americans. - Enabulele Jr., Osemwengie Skelly. (Tufts Archival Research Center, 2017)
Youth is an important time during development in which behavioral patterns are established. Unhealthy risk behaviors are often established during this period and persist into adulthood (CDC, 2016). However, they are quite preventable, making youth an appropriate time to learn about the dangers of unhealthy risk behaviors (CDC, 2016). Youth risk behavior is of great public health importance because it is the age at which young people are beginning to establish lifelong healthy behaviors that can help them avoid preventable morbidity in adulthood; many of which are linked to risk behavior initiation in their youth (CDC, 2016). There are a number of public health strategies to counteract risk behaviors among youth including the family dinner. Family dinner frequency and duration are important aspects of dinners that moderate its effectiveness in strengthening the parent-child relationship and preventing risk behaviors and outcomes among youth. The purpose of this study is to ascertain what the relationship between family dinner frequency and duration and the prevalence of risk behaviors and outcomes including tobacco use, academic achievement, and overweight status as well as to determine if this relationship differs among African-American youth in comparison other youth. The results of this study will be presented as an analysis of the association between mean number of family dinners per week and the outcomes as well as a measure of association between dinner duration and the prevalence of the outcomes for African-American youth in comparison with non-African-American youth in the sample.